Biosafety threats of the rapidly established labs for SARS-CoV-2 tests in China. (October 2020) - Yuan, Dan; Gao, Wenfeng; Liang, Shu; Yang, Shujuan; Jia, Peng
Abstract: To increase the capacity of identifying coronavirus disease 2019 (COVID-19) infection, many Biosafety Level 2 (BSL-2) labs have been established in a short period of time for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) nucleic acid tests all over the world. However, their biosafety has not been evaluated, which could have been the first gateway to SARS-CoV-2 transmission. During 9–11 March 2020, the first comprehensive evaluation of the biosafety in all 89 labs qualified for conducting SARS-CoV-2 tests in Sichuan Province of China was conducted. The degree of compliance with 39 criteria in five categories was evaluated: biosafety requirements for lab activities (14 criteria), sample transfer, acceptance and management (6 criteria), waste management (9 criteria), personnel training and protection (4 criteria), and lab environmental disinfection, emergency plans and accident handling (6 criteria). Our results revealed that, although an overall median compliance rate of 94.6% for 39 criteria, only four of 89 labs met all of them. Criteria in personnel training and protection have been most satisfactorily met, followed by lab environmental disinfection, emergency plans and accident handling. The most severe risk was the lack of automatic doors at the main entrance or in core operation areas, especially among labs in CDC and hospitals. This risk, together with failure for keeping pressure in the core operation areas 25 ± 5 Pa (mainly among labs in the third-party testing agencies), may cause accidental exposure to biological agents from lab activities. Other severe risk included failure for standard labeling of SARS-CoV-2 wastes and lacking regular monitoring of sterilization effects. Our findings would provide experiences and lessons for strengthening lab biosafety in other Chinese provinces, and also serve as an important reference for many other countries where such labs are being or will be quickly built for fighting the COVID-19. The information of lab safety should be considered to be internally linked to the national intelligent syndromic surveillance system (NISSS), for better improving the safety of the labs at the greatest need and facilitating more comprehensive surveillance of risk for disease outbreak.